Dressings as an adjunct to pressure ulcer prevention: consensus panel recommendations. Issue 4 (3rd March 2014) - Black, Joyce; Clark, Michael; Dealey, Carol; Brindle, Christopher T; Alves, Paulo; Santamaria, Nick; Call, Evan
Abstract The formulation of recommendations on the use of wound dressings in pressure ulcer prevention was undertaken by a group of experts in pressure ulcer prevention and treatment from Australia, Portugal, UK and USA. After review of literature, they concluded that there is adequate evidence to recommend the use of five‐layer silicone bordered dressings (Mepilex Border Sacrum® and 3 layer Mepilex Heel® dressings by Mölnlycke Health Care, Gothenburg, Sweden) for pressure ulcer prevention in the sacrum, buttocks and heels in high‐risk patients, those in Emergency Department (ED), intensive care unit (ICU) and operating room (OR). Literature on which this recommendation is based includes one prospective randomised control trial, three cohort studies and two case series. Recommendations for dressing use in patients at high risk for pressure injury and shear injury were also provided.